(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
The integration of Artificial Intelligence (AI) into digital learning platforms has transformed educational experiences by enabling personalization at an unprecedented scale. This article explores the role of AI in creating personalized digital learning experiences, examining its impact on student engagement, achievement, and instructional effectiveness. Through a review of current applications, challenges, and future directions, this study provides a comprehensive understanding of how AI is shaping the future of education. Personalized learning systems powered by AI can meet the varied requirements of students by creating unique lessons for each individual based on their strengths, weaknesses, learning style, and aptitude. Students may have more meaningful learning experiences, improve their grades, and ultimately become topic masters by leveraging AI to personalize educational materials and teacher guidance. The learner is given paramount importance in personalized learning. A personalized learning plan is based on a thorough analysis of each student’s abilities, areas for improvement, areas of interest, and preferred methods of learning.